Surface-initiated reversible addition–fragmentation chain transfer polymerization from "clickable" polypropylene surface modified by iodine plasma activation. (September 2015) - Couturaud, B.; Mas, A.; Robin, Jean J.
Graphical abstract: Highlights: Modification of polymeric surfaces by iodine plasma treatment. Click chemistry onto functionalized polyolefin surfaces. RAFT mediated graft polymerization of hydrophilic monomers from surfaces. Improvement of hydrophilicity of polyolefine surfaces. Abstract: An iodine modified polypropylene surface was synthesized by iodine plasma activation. The obtained polypropylene surface was found to be a useful platform for secondary reactions. For instance, an azide-functionalized PP was prepared by nucleophilic exchange reaction. The surface was proven to be reactive toward R group of an alkyne modified RAFT agent via the copper-catalyzed azide–alkyne cycloaddition. RAFT mediated graft polymerization of methacrylic acid was carried out and lead to a controlled polymerization from the surface. Characterizations of the modified surface and the grafted polymers were performed through FTIR-GATR, XPS, AFM and colorimetric assays.